Jejak Islam di Spanyol dan Dampaknya terhadap Perkembangan Renaissance di Eropa - Muhammad Basri; Nur Hijriyati Waisa; Salsabila Aulia (Universitas Palan, 2024)
This article examines the significant role of Islam in Spain, or Al-Andalus, and its profound impact on the development of the Renaissance in Europe. Focusing on “Islamic Traces in Spain,” this article describes the long and prosperous period of Al-Andalus for more than seven centuries. The aim of the research is to explore the cultural, scientific and intellectual influence of Islam in Spain on European civilization. The research methodology involves historical and literary analysis to explore the contribution of Islam in shaping the intellectual foundations of Europe. Major findings include improvements in science, art, and wisdom that came from cultural contact between the Islamic world and Europe. The conclusion of the article summarizes that the Al-Andalus period had a significant impact in shaping a more modern European civilization. Islam's contribution to the European Renaissance provided an important impetus for the emergence of rational thought and scientific research. The implications of these findings pave the way for understanding the complex relationship between Islamic and European civilizations and their long-term impacts. This article has the potential to provide valuable insights for further research on cultural interactions and intellectual developments along the Islamic Trail in Spain..